"Home at heart": The Experimental Use of Language in the Poetry of Gerard Manley Hopkins and E.E. Cummings. - Stickney, Mary Margaret (My University, 1985)
Gerard Manley Hopkins and E.E. Cummings are both known for their innovative use of language. While each developed widely divergent styles, a study of their experimental approaches to language, particularly their use of deviant syntax, a syntax which violates existing linguistic norms, may provide valuable insight as to the comparative relationship between syntax and aesthetics in their poetry. Perceptual, emotional and conceptual aesthetic effects are achieved through the employment of similar syntactic devices such as deviant formation of words, shifts in the function of words and shifts in word order. The resulting dramatic and perceptual precision of the two poets' language is no less significant than its metaphorical and analogical functions. Spatial, visual and musical analogies from the arts provided both Hopkins and Cummings with paradigms for structuring the elements of language in new ways in order to achieve greater expressive power and imaginative precision. The 'housing' of the deepest areas of human experience in language, particularly through deviant syntax, is the achievement of each of these highly distinctive poets.
Keywords: English Language and Literature; English Language and Literature